Formen und Häufigkeit von Sportverletzungen an der Internatsschule für Schisportler in Stams und allgemeinbildenden Schulen in Tirol - Greier, K. (Sport-Orthopädie - Sport-Traumatologie, 2002)
Diese Studie fasst die Unfälle im Zeitraum 1990-2000 an einer hochleistungsorientierten Sportschule und an allgemeinbildenden höheren Schulen zusammen. Bei den Schisportlern dominieren die Verletzungen der unteren Extremität, während bei den Schülern der allgemeinbildenden höheren Schulen Hand- und Armverletzungen am häufigsten auftreten. Im Hinblick auf die Diagnosen konnten an der Schisportschule Stams hauptsächlich Frakturen und Bandrupturen beobachtet werden, während an den Regelschulen die Distorsionen vorherrschen. This study dealt with sport injuries occuring in a high-achievement orientated sports school and in regular high schools between 1990-2000. According to statistics, a large percentage of sport injuries occur during school sport. The boarding school for skiers in Stams/Tirol, from which many world champions and winners of Olympic medals have come from, assumes here a special position. Essentially, this type of school differentiates itself from other schools due to the increased stress from training and numerous competitions. The injuries of skiing sport students mainly occur in the legs and those students attending a regular high school tend to have injuries occuring more in the arms. The diagnostic results show that the injuries of students in the ski-school in Stams were mainly fractures and torn ligaments whilst the sport injuries of students in the general high school were mainly distorsions.